Kajian kualitas layanan dan harga terhadap loyalitas konsumen melalui kepuasan pelanggan sebagai variabel mediasi selama masa transisi covid-19 : studi kasus pada hotel bintang IV di Jember - Sandy, Syah Riza Octavy; Jatmiko, Hadi (Sadar Wisata: Jurnal Pariwisata, 2023)
The Jember Branch of the PHRI Association (Persatuan Hotel dan Restoran Indonesia) as a reference in this study to stakeholder partners and exclusively to hotel service entrepreneurs for reference when deciding policies to deal with hotel marketing strategies against the transitional conditions of the Covid-19 pandemic and after. This research uses quantitative research methods. Hotel visitors in this study as a population. This research started from a survey with a test of research instruments. Furthermore, obtaining valid instruments, then conducting surveys to explore information through interviews and questionnaires to obtain primary data and secondary data. The data is processed using statistical processing applications. The next stage is to compile a final report based on the results of data analysis and scientific publications as the output of this research. The results of this study show that service quality has an influence on customer loyalty and satisfaction at Bintang IV Hotels in Jember Regency. Price has an influence on customer loyalty and satisfaction at the IV Star Hotel in Jember Regency. Customer satisfaction has an influence on customer loyalty and influences through the relationship between the influence of service quality and price on customer loyalty to the IV Star Hotel in Jember Regency